PENGARUH KUALITAS ASET, LIKUIDITAS, DAN RENTABILITAS TERHADAP CAPITAL ADEQUACY RATIO (CAR) PADA PERUSAHAAN PERBANKAN DI INDONESIA PERIODE 2013 – 2015 - Hidayati Pujiastuti, 13.05.51.0175 (Students' Journal of Economic and Management, 2017)
The Bank is a trust institution that has an intermediary function, helps the payment system and implements government policy monetary policy. The function proves that the existence of a healthy bank, has a relationship with the economic growth in a country. Banking is one of the important sectors in Indonesia. In recent years, the condition of banking in Indonesia has begun to show progress towards improvement although it is still experiencing difficult stages in order to balance the financial position. This is reflected in positive developments in funding, capitalization, profitability, and quality of productive assets. Capital Adequacy Ratio (CAR) is the ratio of capital used to measure the health of the bank. CAR is based on the ratio of capital to Risk Weighted Assets (ATMR). In accordance with Bank Indonesia regulation, banks must have a CAR of 8%.The purpose of this study is to examine the effect of Asset Quality (NPL), Liquidity (LDR), and Rentability (ROA) on Capital Adequacy Ratio (CAR) in banking companies in Indonesia and listed on Indonesia Stock Exchange (IDX) 2015. The data used in this study comes from the Indonesia Stock Exchange (IDX). The sampling method used purposive sampling method with 15 banking companies. This research uses regression analysis method of panel data. The results showed that the quality of assets (NPLs) did not affect the Capital Adequacy Ratio (CAR), Liquidity (LDR) had an effect on Capital Adequacy Ratio (CAR), and Rentability (ROA) influenced Capital Adequacy Ratio (CAR). Keyword: Asset Quality, Liquidity, Rentability, Capital Adequacy Ratio